Physicochemical properties of virgin coconut oil extracted from different processing methods - Tengku Mansor, Tengku Salwani; Che Man, Yaakob; Mustafa, Shuhaimi; Mohd Jaih, Abdul Afiq; F. K. M., Ku Nurul (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Virgin Coconut Oils (VCO) were prepared from fresh-dry (grated coconut route), chilling and thawing, enzymatic and fermentation method in this study. All of the VCO produced conformed physicochemically to the standards established by the Asian and Pacific Coconut Community (APCC) and Codex Alimentarius Commission. The highest FA (fatty acid) is lauric acid in all of the VCO and ranged from 46.36-48.42 %, while the principal TAG (triacylglycerol) is LaLaLa (La: Lauric) with 17.94-19.83 % of the total TAG. Tocopherol analysis showed the presence of beta, gamma and delta tocopherols at low levels. In all, the physicochemical, FA and TAG analyses of the VCO extracted from different methods showed some significant differences, while the tocopherol content does not differ significantly among the different types of extraction methods used.